Clinical efficacy and safety of sodium-glucose cotransporter protein-2 (SGLT-2) inhibitor, glucagon-like peptide-1 (GLP-1) receptor agonist, and Finerenone in type 2 diabetes mellitus with non-dialysis chronic kidney disease: a network meta-analysis of randomized clinical trials - Guo, Jingyi; Wei, Maoying; Zhang, Wenhua; Jiang, Yijia; Li, Aijing; Wang, Churan; Yin, Dan; Sun, Anning; Gong, Yanbing (Frontiers in Pharmacology, 2025)
ObjectiveTo investigate the safety and clinical efficacy of sodium-glucose cotransporter protein-2 (SGLT-2) inhibitors, glucagon-like peptide-1 (GLP-1) receptor agonists and Finerenone in treating patients with type 2 diabetes mellitus (T2DM) combined with non-dialysis chronic kidney disease (CKD).MethodsCochrane Library, PubMed, EMBASE, Web of Science, CNKI, CQVIP database, and WanFang from their inception up to November 2023 were searched to compare the efficacy and safety of SGLT-2 inhibitors, GLP-1 RA receptor agonists and Finerenone in the treatment of T2DM patients with non-dialysis CKD. To assess the methodological quality and risk of bias in the included studies, we utilized the Cochrane Risk of Bias Assessment tool (RoB 2.0). The confidence of evidence was examined using Confidence in Network Meta-Analysis (CINeMA). Traditional meta-analysis of variables was conducted using Stata 17.0 software with a random-effects model. We assessed publication bias using funnel plots and explored potential sources of heterogeneity through subgroup analysis.ResultsA total of 39 studies (99,599 patients) were included. Compared to Placebo (PBO), SGLT-2 inhibitors demonstrated superior efficacy in reducing glycosylated hemoglobin (HbA1c) (MD = −0.33; 95%CI: from −0.52 to −0.15), systolic blood pressure (SBP) (MD from −5.52 to −1.50; 95%CI from −8.80 to −0.23), body weight (MD from −3.81 to −1.29; 95%CI from −6.34 to −0.84) and diastolic blood pressure (DBP) (MD = −1.86; 95%CI: −3.18, −40.54). The efficacy of Liraglutide in reducing Low-Density Lipoprotein Cholesterol (LDL-C) surpassed that of other agents (MD from −1.58 to −1.41; 95%CI from −2.05 to −0.81). Finerenone significantly reduced SBP (MD = −1.65; 95%CI: −2.48, −0.81) compared to PBO. According to the SUCRA based relative ranking of treatments, Empagliflozin was the most effective in reducing HbA1c and DBP. Semaglutide was the least harmful to estimated glomerular filtration rate. Liraglutide was the most effective in reducing LDL-C. Bexagliflozin, Canagliflozin were the most effective in reducing SBP and body weight. Finerenone had the lowest incidence of urinary tract infection, Hypoglycemia was the lowest in the Luseogliflozin group. Ertugliflozin was the least likely to cause acute kidney injury. Canagliflozin had the lowest probability of any adverse event.ConclusionThe safety of these drugs has been confirmed, except for some special drugs. SGLT-2 inhibitors had a preferential glucose-lowering and weight-loss function, GLP-1 receptor agonists had a preferential lowering of LDL-C and blood glucose, and Finereone significantly reduced SBP compared with PBO. Systematic Review Registration: PROSPERO, CRD42024571544.